Tradisi Intrega Nan Kakorok Pada Suku Assae Berliuk di Desa Lakekun Barat Kecamatan Kobalima Kabupaten Malaka - Jonavia L.L. De Carvalho; Antonius Bere; Clotilde Seran (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research is entitled the intrega nan kakorok tradition of the Assae Berliuk tribe in West Lakekun Village, Kobalima District, Malaka Regency. The aim of this research is to understand the implementation process carried out during the intrega nan kakorok ceremony. This study used descriptive qualitative method. The results of the research show that the Intrega Nan Kakorok tradition among the Timor Leste people of the Assae Berliuk Tribe in West Lakekun Village, Kobalima District, Malacca Regency really upholds this tradition because they consider that intrega nan kakorok is a culture that has been passed down from generation to generation. Intrega is submission, nan is meat and kakorok is neck. Intrega nan kakorok is carried out to commemorate the deceased or express feelings of sorrow or intrega nan kakorok is expressed in the form of conditioning oneself in a certain attitude. The Intrega Nan Kakorok tradition is a final ceremony of respect for uncle, where a ceremony will be carried out in the form of slaughtering an animal (buffalo) which will be given to uncle or to the family who has the right to the meat. The intrega nan kakorok ceremony can only be performed when there is a death or a time of mourning. For all the East Timorese people of the Assae Berliuk Tribe in West Lakekun Village, Kobalima District, Malaka Regency, it is hoped that they will continue to maintain and always uphold this traditional heritage for their children and grandchildren so that its historical value is maintained, remains and is always developed further.